A construção da imagem da mulher no cinema de ficção produzido na Amazônia paraense - SOUSA, Raissa Lennon Nascimento (Universidade Federal do Pará, 2018)
The main goal of this resarche was to observe the construction of the woman’s imagine in the fiction movies made at paraense Amazon, according to the constant speeches in the plots and its main iconic elements. We can understand that the presence of women in cinema is very significant, assuming relevant characters in contemporary. Thus, contemporary movies highlight the woman as the main subject of the plots selected. The analysis corpus consists of short movies released in a period of effervescence of Para cinema, from 2010 to 2012: " Matinta " (2010 ) , Fernando Segtowick ; " Bordering the Asphalt " (2011 ) , by Jorane Castro ; "Birds Walkers and Bois Flying " (2011 ) , Luiz Arnaldo Campos ; and " Juliana Against Jambeiro Devil by John the Baptist Heart " (2012) , Roger Elarrat . Authors from the area of communication and especially the cinema , linguistics and Philosophy were used in analytical construction of the chosen corpus , as Michel Courtine (2005 ) , Jacques Aumont (2002 ; 2008) , Walter Benjamin (1994 ) , Pêcheux (1995 ; 1997) and Michel Foucault (2000 ; 2008) . Based on the four movies analyzed, we can conclude that the image of contemporary Amazonian woman in fiction movies is the women who while maintaining submission elements in relation to man , they conquisted their space using courage, work, seduction and femininity, spaces of action and emancipation in the environments they live ( urban or rural ).